Multifunctional Nanomaterials Synthesis, Properties and Applications - Yadav, Raghvendra Singh (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This book is a collection of review articles and research articles, which was published in the Special Issue "Multifunctional Nanomaterials: Synthesis, Properties and Applications" of the International Journal of Molecular Sciences.